2018
DOI: 10.1103/physrevlett.121.167401
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Profiles of Valley Polarization in Single-Layer MoS2 and MoSe2

Abstract: In this letter we present photoluminescence measurements with different excitation energies on single-layer MoS2 and MoSe2 in order to examine the resonance behavior of the conservation of circular polarization in these transition metal dichalcogenides. We find that the circular polarization of the emitted light is conserved to 100 % in MoS2 and 84 %/79 % (A/A − peaks) in MoSe2 close to resonance. The values for MoSe2 surpass any previously reported value. However, in contrast to previous predictions, the degr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 32 publications
4
23
0
Order By: Relevance
“…49 Scattering process involving zone boundary phonons are also believed to be responsible for the notorious valley depolarization, which represents a serious obstacle for valleytronics. [50][51][52] After we have confirmed that our approach based on DFT derived bandstructure and the model dielectric function defined in Eq. (2) adequately describes key elements of the photoemission and the EELS data in the energy region of the A and B-excitons we focus now on the momentum dependence of the C-exciton.…”
Section: Eelssupporting
confidence: 61%
“…49 Scattering process involving zone boundary phonons are also believed to be responsible for the notorious valley depolarization, which represents a serious obstacle for valleytronics. [50][51][52] After we have confirmed that our approach based on DFT derived bandstructure and the model dielectric function defined in Eq. (2) adequately describes key elements of the photoemission and the EELS data in the energy region of the A and B-excitons we focus now on the momentum dependence of the C-exciton.…”
Section: Eelssupporting
confidence: 61%
“…Another striking difference between TMD materials is the amplitude of spin/valley polarization for excitons. Although strong valley polarization and valley coherence have been measured in WSe 2 , WS 2 , and MoS 2 MLs, the polarization in MoSe 2 and MoTe 2 MLs is very weak 35,36 except under quasi-resonant excitation where significant polarization has been measured for the trion in MoSe 2 37 . Recently, it was proposed that a crossing of bright and dark exciton dispersion curves combined with a Rashba effect associated with local fluctuations of electric field can lead to very fast spin relaxation 11 .…”
Section: Discussionmentioning
confidence: 97%
“…The emitted light gives information on spin and valley dynamics in time-integrated PL experiments. The circular polarization, P c , in time-integrated experiments depends on the exact ratio of PL emission time τ PL to depolarization time (τ depol ) as P P = /(1 + ) τ τ c 0 PL depol , where P 0 is the initially generated polarization, which could depend on the excitation energy 169,170 .…”
Section: Spin-valley Polarizationmentioning
confidence: 99%